The Hamiltonian approach to dynamic economics - Cass, David; Shell, Karl. (New York : Academic Press, 1976)
The papers in this volume can be thought of as attempts at providing some unification of the theory of heterogeneous capital. The major topic, although by no means the only one, which the authors investigate here is the stability of long-run steady-state equilibrium in models of heterogeneous capital accumulation. However, the basic techniques used in this investigations have wide application to economic dynamics in all its manifestations. This follows from the observation that the economic growth models which the authors treat individually belong to a class of general inter-temporal economic models which is essentially representable by what they call a Hamiltonian dynamical system.
"Originally appeared as papers in the Journal of economic theory, volume 12, number 1 (February 1976)."
Includes bibliographical references and index.
rpm 28/08/2017
Loans
Keywords: Economics, Mathematical; Statics and dynamics (Social sciences)